ENERGY, SECURITY, CLIMATE: CONVERGING SOLUTIONS (Utah Environmental Law Review; Vol 29 No 1 (2009), 2009)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} So often our challenges seem daunting. So often we fail to address them until it’s too late; this can be said of everything from terrorism to Social Security. It is true of energy policy as well. Since the first oil embargo in the early 1970s, the nation seems to have sleepwalked through three decades of indecision and irresolution with respect to energy. When prices rise, perhaps we see a flurry of interest in alternative energy options. But almost inevitably the prices fall again, and, despite the damage and the remaining vulnerability, the interest in alternatives flags. Today, with oil prices nudging at the $100 level, it would be a good time to recognize that a sustained, focused interest in energy policy is needed. Even more, we need a change in attitude, recognizing that the challenges posed by energy policy—from national security to economic prosperity to preservation of the global atmosphere and climate—are profitable and rewarding to solve. Meeting the energy policy challenge isn’t something that needs to be painful, or even to require large changes in our lifestyles or communities. In contrast, the converging solutions to our energy, security and climate problems will be relatively easy and affordable to solve. Their magnitude is intimidating, but the fact is that these problems are indeed solvable. We should quit running away from them and address them head-on, with a set of complementary policies that reduce costs to consumers and taxpayers, that reduce our carbon emissions, that create a more resilient and productive economy, and that strengthen our nation and reduce its exposure to hostile organizations and regimes around the world. Sounds like a tall order, but it really isn’t for a nation with our resources, financial depth, technical and scientific strength, and world presence.